An efficiency analysis of the parallel multitransputer implementation of two-level optimization algorithms - Sadecki, Jan (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents an approach to improve the efficiency of some two-level optimization algorithms by their implementation in parallel MIMD multiprocessor systems. Diagonal decomposition dynamic programming and parametric optimization methods are considered, and some concepts of their parallelization are discussed.
Keywords: parallel computations; multitransputer systems; parallel optimization algorithms; two-level optimization methods